Hybrid Approach for Securing Image Tempering in Cloud Storage - Sharma, Sachin; Singh, Brajesh Kumar; Garg, Hitendra (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The global appeal of leveraging advanced computational infrastructure provided by cloud-based multimedia systems has become increasingly evident. Nevertheless, the security challenges associated with these cloud-based systems, which involve third-party servers, cannot be overlooked. To tackle these security concerns effectively, a proposed solution involves encrypting the data in a way that makes it indecipherable to the cloud data centers. This work introduces an image encryption method built upon the Permutation Ordered Binary (POB) Number System. This technique entails the partitioning of the image into randomly generated shares, which can subsequently be stored in cloud data centers. Furthermore, the proposed method guarantees the integrity of these shares at the individual pixel level. If any unauthorized modifications occur on the cloud servers, the system can accurately detect the altered pixels by leveraging authentication bits and precisely locate the tampered area. This tampered section is also reflected in the reconstructed image, which is accessible to authorized users. The accuracy of tamper detection has been thoroughly evaluated on a pixel-by-pixel basis, demonstrating remarkable effectiveness in a wide range of tampering scenarios.